Welcoming in Foster Families: Experience Creating a New Culture - Gvaldaitė, Lijana (Socialinė teorija, empirija, politika ir praktika, 2017)
This article discusses the welcoming concept and experience in fostering a child in Lithuania. It is important to study the phenomenon of foster families, since a very high level of institutionalization exists within the sphere of child care in the country and the number of families to potentially welcome children abandoned by their parents is decreasing. Another reason is that the culture of gratuitousness and solidarity is very scarce; therefore, it is crucial to analyze the families that positively experience fostering and represent the best practices in this field. Such conception of welcoming is linked with the procreative nature of the family discussed in Christian anthropological literature, which is understood not only as an ability of a couple – male and female – to generate new life, but also as a generation in spiritual, cultural and social ways. The relationship of a man and a woman, in its differences and complementation, if only it is open and alive, can be generative and acceptive of others, able to give space to, embrace and support even distant and unknown people. To explain welcoming, the concept of a gift is presented with reference to different authors of Christian anthropology, philosophy and theology – K. L. Schmitz (1980), Schildler (2011), Lopez (2014 a, 2014 b), Giussani (2012), Laumenskaitė (2010). This complex concept is revealed as a freely and in an unmerited way received gift, related to the nature of gratuity in the relationship with God. In seeking to introduce the most significant experiences of fostering in families, 10 semi-structured interviews were conducted with 5 foster families – married couples (wives and husbands were interviewed separately), using the qualitative interview methodology. Certain families, those related to the NGO SOTAS, which have positive experiences of fostering a child that is not of a relative origin, were purposefully selected for this research. It was also revealed that they are practicing Christians (not all of them Catholics) and belong to Christian communities. This research has highlighted that the reasons and paths of becoming foster parents of each family are different; however, in general, it is possible to say that it is related to the need to share and give oneself to others – this as a gift that they recognize to have experienced in their childhood or being adults and are still experiencing in their lives. Sharing this desire in their families and with their children (all families have their own children, most of whom are adults) formed the decision to foster children who lost parental care. Nevertheless, the main influence for their decision to foster children was their faith in God, participation in the community, meaningful events and meetings. Some of them called it the calling, which they recognized as the call of God to fulfill his will; they also perceive a child as a given, as a gift of God. For families, fostering is a new and different form of parenting (not the same as parenting their own children), where the experience of unconditional love grows. However, such attitude of foster parents towards their children, which is not automatic and easy, does not resolve problems and dramas of foster parents. Nevertheless, it changes appearance and increases consciousness and liberates them from limitations and the fear of making mistakes. Therefore, together with inevitable devotion and difficulties, it is the experience of joy, fulfillment and gratitude that a child exists and changes the life of the whole family. In the article, the problem of a child’s relationships with his family of origin is treated as well, a problem which is frequently discussed among various researchers and specialists because of its meaning and benefit for a child. Fostering puts a child in the situation of a double belonging (Roncari, 2014, and others), it is a crucial and most dramatic point for all participants of foster care – firstly, for the child. Thus, the main task of foster parents is to rebuild the lost relationship, unconditionally giving themselves, but not replacing and devaluing the families of origin, which remains for a child as a fact, the aspect of truth about him. Having generalized the material of the interviews with foster families, a particular feature of their experience can be highlighted: it is the unconditional attitude and openness to the child and the reality, which obviously has influence on the entire fostering process. These fostering families receive from within their own families, as well as their relatives, communities and SOTAS, which is the organization they come to for consultations and participation in the self-help groups of fostering families. Finally, the experience of faith is the main basis for these families and the basis of their conception of education and relationships. These experiences of foster parents witness about a hard, but attractive form of being a family in which they find the calling and this inevitably changes social environment as well. This shows how families can be a generative place not only for their children, but also for others, thus contributing to the common good.